WorldSkills UK Training Managers: Midas Touch or Fool's Gold? - Stephanie Wilde; Susan James Relly (International Journal for Research in Vocational Education and Training (IJRVET), 2015)
This article focuses on the role of training managers (TMs) in UK participation in WorldSkills Competitions (WSC). The TM role is outlined, according to the perceptions of the TMs, and there is analysis of the benefits to them of participation, as well as the barriers they face, and the benefits and barriers available to participating further education colleges and employers. The article is based on analysis of semi-structured interviews with almost the full cohort of UK TMs preparing competitors for WorldSkills Brazil 2015, and concludes with reflections on the vision and purposes of UK WorldSkills participation.
Keywords: 330; worldskills; training managers; qualitative research; skills competitions; vocational training and education